Russian institutional development: challenges to inbound investments and implications for government policymakers. (2015) - Yukhanaev, Andrey; Perényi, Áron; Fallon, Grahame; Roberts, Joanne
This paper sets out to contribute to the literature by investigating the institutional arrangements facing investors in Russia, the extent to which they had been reformed, and the resultant impact on the willingness of foreign-owned TNCs to commit inbound foreign direct investment (IFDI) to this high-risk transition economy. The degree to which institutional factors explain Russia's persistent underperformance in terms of IFDI is assessed through the review of the academic literature and other documentary sources. Making use of the corruption perception index, ease of doing business, world governance indicators and index of economic freedom (IEF) data, we analyse the provenance of Russia's IFDI-related institutional reforms since the late 1990s until the end of 2013. Given the international isolation of Russia after its annexation of the Crimea and the collapse of the oil price, the paper argues that in order to achieve a sustainable economic development, the Russian Government must implement substantial shifts in the design and functioning of its national institutions.